Review of Turkish-Israeli Relations Based on Neo-Realism - Soleimani Jouneghani, Arash (Journal of History Culture and Art Research, 2018)
Basically, the two countries, Turkey and Israel, apart from their relations with Iran, are the important and influential countries in the region and the global developments associated with the Middle East, so efforts to better understand the two countries help to answer the questions about these two countries. This research, along with the historic genealogy of Turkey-Israel relations has attempted to address the roots of Turkey-Israel Westernization and its relation with the proximity of the two countries and the formation of strategic cooperation between Ankara and Tel Aviv. Our important issue in this study is to examine the relation between Turkey and Israel from a historical point of view, based on the neo-realism approach in the field of foreign policy.